PRINCIPAL COMPONENT ANALYSIS WITH NEURAL NETWORK AND DNA SEQUENCE ANALYSIS - Oliveira, Marcus Rogério de (Revista Interface Tecnológica, 2005)
The Artificial Neural Networks are versatile tools for a number ofapplications. VV1th their many configuritions ofparameters and architectures, Artificial Neural Networks are used in Bioinforrnatics and other areas. This work presents an Artificial Neural Network that implements Principal Component Analysis (PCA) and performs DNA sequence analyses.
Keywords: Artificial Neural Networks; Principal Component Analysis; Hebbian Neural Network Neuron